2007
DOI: 10.1016/j.genhosppsych.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders among persons with heart disease — results from World Mental Health surveys

Abstract: Objective-While in western countries depression and heart disease often co-occur, less is known about the association of anxiety and alcohol use disorders with heart disease and about the crosscultural consistency of these associations. Consistency across emotional disorders and cultures would suggest that relatively universal mechanisms underlie the association.Method-Surveys in 18 random population samples of household-residing adults in 17 countries in Europe, the Americas, the Middle East, Africa, Asia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(85 citation statements)
references
References 39 publications
5
77
1
2
Order By: Relevance
“…Also, studying the factors related to HRQL at 6 months, the same authors observed that depression, assessed by the 28-item General Health Questionnaire, a previous history of Coronary Heart Disease (CHD), or the associated comorbidity had a negative effect on quality of life, with a worse clinical course in these patients when compared with those without these conditions. This results are in agreement with Ormel et al (Ormel et al, 2007) and Höfer et al (Höfer et al, 2005) who found that depression and anxiety are the most significant factors influencing HRQL in patients with heart disease, and with McBurney et al (McBurney et al, 2002), who observed that the presence of other illnesses had a negative effect on the PCS-12 seven months after an AMI, and that having more comorbidity tends to lower HRQL in all dimensions.…”
Section: Factors Related To Health Related Quality Of Life In Coronarsupporting
confidence: 92%
“…Also, studying the factors related to HRQL at 6 months, the same authors observed that depression, assessed by the 28-item General Health Questionnaire, a previous history of Coronary Heart Disease (CHD), or the associated comorbidity had a negative effect on quality of life, with a worse clinical course in these patients when compared with those without these conditions. This results are in agreement with Ormel et al (Ormel et al, 2007) and Höfer et al (Höfer et al, 2005) who found that depression and anxiety are the most significant factors influencing HRQL in patients with heart disease, and with McBurney et al (McBurney et al, 2002), who observed that the presence of other illnesses had a negative effect on the PCS-12 seven months after an AMI, and that having more comorbidity tends to lower HRQL in all dimensions.…”
Section: Factors Related To Health Related Quality Of Life In Coronarsupporting
confidence: 92%
“…9,10 For instance, in a study by Kimmel et al, the rates of hospitalization due to psychiatric illnesses among patients with ESRD aged 65 years and older were significantly higher for those with ESRD than those with ischemic heart disease, cerebrovascular disease, and peptic ulcer disease.…”
Section: Prevalence Rates Of Depression and Anxietymentioning
confidence: 99%
“…In public health research, indirect costs are most often operationalized as time till return to work or productivity loss of patients according to the human capital method. Patients with CAD are at increased risk of developing mental disorders (OR = 1.9-2.7) [5]. These comorbid mental disorders have frequently been shown to impair health outcomes in CAD patients such as increased mortality [6] and diminished quality of life [7,8].…”
Section: Mood Disorders (Icd-mentioning
confidence: 99%